Workplace Discipline and Employee Performance at the Bangka Pratama Tax Service Office: The Influence of Work Competency, Commitment, and Motivation - Listyorini, Etty; Reniati, Reniati; Daulay, Pardamean (JURISMA : Jurnal Riset Bisnis & Manajemen, 2024)
One of the key elements that determine whether a business is successful in reaching its objectives is employee performance. Technical issues are not the only factors that impact employee performance; competence, dedication, and motivation at work are also important factors. However, sound discipline is required to support each of these qualities. Using quantitative methods and a sample of 94 The KPP Pratama (Kantor Pelayanan Pajak Pratama/Primary Tax Office) Bangka employees, this study seeks to ascertain the extent to which the independent variables (competence, commitment, and work motivation) impact the engagement variable (employee performance) and the intervention variable (discipline). This study employed the Structural Equation Modeling with the Partial Least Square (SEM-PLS) technique for data analysis. The analysis's findings demonstrate that employee performance at KKP Bangka Pratama is positively and significantly impacted by the discipline variable and that competence, dedication, and work motivation have a positive and large impact on both of these variables.